Outcome of Stone Fragmentation with Pneumatic and Ultrasonic Lithotripter During Percutaneous Nephrolithotomy (Bangladesh Journal of Urology, 2020)
Background of the study: Percutaneous nephrolithotomy (PCNL) is the gold standard treatment for kidney stones larger than 2 cm. PCNL has replaced open surgical removal of large or complex calculi at the most institutions. The success of PCNL is related to the ability to achieve an optimum access tract and proper fragmentation. A wide range of lithotripsy techniques are currently available. One of these is ultrasonic lithotripsy, in which the stones are fragmented and sucked out simultaneously. This technique induces minimal tissue injury and could be considered as a standard modality for PCNL. The pneumatic lithotripter uses pneumatic ballast, which crushes the stones without producing any thermal effects. Because this mechanical energy passes along the metal wire to the stone, the probe works like a chisel on the stone surface. This modality destroys all stones, regardless of their composition. There were very few studies had been done in this context in our country, so I had decided to do this study to compare the outcome of stone fragmentation with pneumatic and ultrasonic lithotripter during percutaneous nephrolithotomy.Objective: To compare the outcome of stone fragmentation with pneumatic and ultrasonic lithotripter during percutaneous nephrolithotomy.Materials & Methods: This Prospective Interventional Study (Quasi Experimental Trial) was performed in Department of Urology, National Institute of Kidney Diseases and Urology, Sher-E- Bangla Nagar, Dhaka during the period from December 2014 to May 2016. A total of 60 subjects will be selected with renal calculi (as per inclusion & exclusion criteria), among these, half of the patients will be group A (using pneumatic lithotripsy) & rest of the patients will be group B (using ultrasonic lithotripsy). The study subjects were underwent PCNL under general anesthesia, half of which used pneumatic lithotripter and rest used ultrasonic lithotripter for stone fragmentation. Above mentioned outcome variables were assessed both per-operative and post-operatively. Data were collected, processed & analyzed. Statistical analysis of relevant variables was done by unpaired Student’s T test and Chi Square test. P value Â0.05 was considered significant.Results: Total 60 patients were selected for study according to the selection criteria. Of the 60 subjects, 30 patients, those who were done PCNL by pneumatic lithotripsy were labeled as Group A and 30 patients, those who were done PCNL by ultrasonic lithotripsy, were labeled with Group B. Distribution of respondents in terms of different parameters is shown in tabulated form and statistical analysis was done in both groups to see statistical significance, p value less than 0.05 was considered significant. The mean stone fragmentation time was 27.23±4.78 (18-38) min in PCNL by pneumatic lithotripsy and those were 23.80±5.30 (13-34) min in by ultrasonic lithotripsy which is statistically significant. Other variables of interest which includes stone clearance rate, post operative haematuria and post operative hospital stay, were not statistically significant.Conclusion: Comparing the findings of the present study, results indicate that stone fragmentation time is lesser in ultrasonic lithotripsy than pneumatic lithotripsy in PCNL which decreases the overall operative time.Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.129-135